KRAS mutational test for metastatic colorectal cancer patients: not just a technical problem. (March 2012) - Molinari, Francesca; Frattini, Milo
Evaluation of: Hamfjord J, Stangel AM, Skrede ML et al. Wobble-enhanced ARMS method for detection of KRAS and BRAF mutations. Diagn. Mol. Pathol. 20, 158–165 (2011). The identification of KRAS and BRAF mutations as predictive molecular alterations of resistance to EGF receptor monoclonal antibody therapy in metastatic colorectal cancer have significantly improved the selection of patients more likely to be eligible for the treatment with these targeted agents. Several methods are available for KRAS and BRAF mutation detection but few studies have compared different techniques, especially in the clinical setting. In this article, we contextualize the wobble-enhanced amplification refractory mutation sequencing method for the identification of KRAS and BRAF mutations with the other methodologies frequently used for the assessment of these alterations in colorectal cancer, discussing advantages and limitations over other frequently used diagnostic methods.